Critical Airway Stenosis in an Adolescent Male With Pompe Disease and Thoracic Lordosis: A Case Report. Issue 7 (1st October 2017) - Brenn, B. Randall; Theroux, Mary T.; Shah, Suken A.; Mackenzie, William G.; Heinle, Robert; Scavina, Mena T.
Abstract : An adolescent male with late-onset Pompe disease (glycogen storage disease type II) presented with a history of restrictive airway disease and a near-cardiorespiratory arrest during anesthesia for a liver biopsy initially thought to be due to bronchospasm. During a subsequent posterior spinal fusion procedure, he suffered cardiorespiratory arrest resulting in the procedure being aborted. Bronchoscopy performed shortly after resuscitation revealed an undiagnosed narrowing of the distal trachea and bronchi. This is the first description of a patient with late-onset Pompe disease with undiagnosed critical tracheal stenosis due to the progression of thoracic lordosis, which was ultimately relieved by posterior spinal fusion.